Mesenchymal Stem Cell physiology can be affected by antibiotics: An in vitro study - Pountos, I.; Georgouli, T.; Henshaw, K.; Howard, B.; Giannoudis, P. V. (Cellular and Molecular Biology, 2014)
The aim of this study was to investigate the effect of antibiotics used in clinical practice on Mesenchymal Stem Cells (MSCs) potential to proliferate and differentiate towards an osteogenic lineage. Trabecular bone was obtained from 10 patients (mean age of 36 years, range 18-72) suffering from long bone fractures. Mesenchymal Stem Cells (MSCs) were isolated and functional assays on their proliferation (CFU-F and XTT) and osteogenic differentiation (alkaline phosphatase activity and total calcium production) were performed. The effect of medium supplementation with gentamicin, vancomycin, benzyl-penicillin, flucloxacillin, cefuroxime and metronidazole was analysed. In concentrations found in peripheral circulation, none of the studies antibiotics had an effect on MSCs ability to proliferate and differentiate towards osteogenic lineage. Vancomycin and gentamicin in concentrations of 200 Î¼g/ml and 75 Î¼g/ml respectively, down-regulated the proliferation and osteogenic activity of MSCs. Some combination of the studied antibiotics found to inhibit both proliferation and osteogenesis. High antibiotic concentrations and the combination of different formulations can have detrimental effects on osteoprogenitor cells physiology and potentially bone healing.